Building Safer and Interoperable AI systems. - Cerf, Vinton G. (Communications of the ACM, 2025)
Thirty-five years ago, the concept of knowledge robots (knowbots) was envisioned as mobile code capable of navigating the Internet, gathering and processing information for users. Today, advancements in AI have brought forth intelligent agents, including large language models (LLMs), that can interact with humans and each other, raising questions about syntax, semantics, and safety in inter-agent exchanges. While these agents hold potential for efficient collaboration and innovation, concerns about ambiguity, miscommunication, and unintended consequences highlight the need for disciplined development and safety standards.